The Impact of Financial Leverage on Firm Performance in Emerging Markets: An Empirical Analysis - Ratna Mutumanikam, Primadonna; Adelin, Dessy (Dinasti Research & Yayasan Dharma Indonesia Tercinta (DINASTI), 2024)
This study examines the impact of financial leverage on firm performance within emerging markets, with a focus on publicly listed firms in countries such as Indonesia, India, and Brazil. Financial leverage, often measured by the debt-to-equity ratio, plays a critical role in determining the financial structure and performance outcomes of firms, especially in economies where capital markets are evolving and subject to unique challenges. Using data from corporate financial statements and applying regression analysis, this study investigates the relationship between leverage and key performance indicators, including Return on Assets (ROA) and Return on Equity (ROE). The results suggest a nuanced relationship, where leverage has both positive and negative effects on performance, depending on market conditions and firm characteristics. These findings provide valuable insights for corporate managers in emerging markets on optimizing capital structure and maximizing firm value. Furthermore, the study underscores the importance of considering economic factors and firm-specific attributes when making financing decisions. Limitations and implications for future research are also discussed.